Music Culture Integration Strategy and City Tagline Innovation As A Push Factor For Ambon To Become A World Music City - Ubjaan, Jusak; Lourens, Samson; Renyut, Selvia F. G.; Jacobs, Samie L (Advances in Social Sciences Research Journal, 2023)
Positioning Ambon as a music city is not without reason; the people of Ambon already have socio-cultural values from music. Music, as one of the sub-sectors of the creative economy, is a source of economic development that can be enjoyed by all groups and is quite eye-catching. On the other hand, city tagline innovation is a tourism revitalization tool that aims to re-image a city. This study aimed to examine the strategy of local music culture and the city tagline innovation policy as a driving factor for Ambon to become the World Music City. This research used explanatory research with qualitative and quantitative approaches. Validity and reliability tests were conducted before the research instruments were used to collect data. The number of respondents was 74 people. Data analysis uses Generalized Structured Component Analysis. The results of the descriptive analysis show the music culture variable with an average score of 4.01, city tagline innovation of 4.15 and Ambon music city of 4.01. The results of hypothesis testing (H1 ) show that exogenous variables significantly affect endogenous variables with a direct coefficient of 0.342 and a critical ratio value of 2.49 *. The hypothesis test (H2 ) shows that exogenous variables significantly affect endogenous variables with a direct coefficient of 0.336 and a critical ratio of 4.09 *. It is recommended that the city government continue to develop supporting facilities such as educational institutions, performance halls, recording studios, development of traditional musical instruments and regular music events.